2004
DOI: 10.1111/j.1399-3054.2004.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen supply on growth, contents of phenolic compounds and pathogen (scab) resistance of apple trees

Abstract: The effect of long-term N-supply on growth, scab resistance and phenolic compounds in the leaves of two apple cultivars was studied. The different pools of phenylpropanoids (hydroxycinnamic acids, dihydrochalcones) and flavonoids (flavonols, catechins, procyanidins) were quanitfied by HPLC from non-infected and inoculated leaves representing different ontogenetic stages. Scab incidence was also evaluated. Strictly following the carbon-nutrient-balance hypothesis, apple trees responded to high N-supply with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
73
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 23 publications
11
73
1
2
Order By: Relevance
“…In contrast, the maximum value of catechin in pear leaves was obtained only at the beginning of September (Colaric et al , 2007 (Table 2). Leser and Treutter (2005) reported that the resistant cultivar Rewena contained more catechins than Golden Delicious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the maximum value of catechin in pear leaves was obtained only at the beginning of September (Colaric et al , 2007 (Table 2). Leser and Treutter (2005) reported that the resistant cultivar Rewena contained more catechins than Golden Delicious.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have shown that high N-nutrition reduced flavonoid accumulation in leaves. This situation is positively correlated to increased susceptibility to scab (Ru¨hmann et al 2002;Leser and Treutter 2005;Strissel et al 2005). The content of phenolics in a plant may be influenced by cultivation conditions (environmental conditions and cultivation techniques).…”
mentioning
confidence: 99%
“…Apple trees respond to a high N-supply by increased shoot growth and the reduced accumulation of total phenolic compounds in their leaves (Leser, Treutter 2005). The application of N might cause a decrease in the content of some phenolics and in the percentage of blush skin of apples (Awad, De Jager 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Heavy nitrogen fertilization supports tree and fruit growth and therefore is a prominent controlling tool for yield. An enhanced vegetative growth of apple trees, however, is often correlated with an increasing susceptibility to pathogens such as V.inaequalis (Leser and Treutter, 2005). This may be due to the concomitant decrease of phenolic compounds by high nitrogen uptake (Leser and Treutter, 2005) indicating that environmental conditions favouring plant growth reduce investment of carbon for defence.…”
Section: Fertilizationmentioning
confidence: 99%
“…An enhanced vegetative growth of apple trees, however, is often correlated with an increasing susceptibility to pathogens such as V.inaequalis (Leser and Treutter, 2005). This may be due to the concomitant decrease of phenolic compounds by high nitrogen uptake (Leser and Treutter, 2005) indicating that environmental conditions favouring plant growth reduce investment of carbon for defence. Kumar and Gupta (1986) observed that a high level of potassium fertilizers increased resistance of apple tree to scab but a similar effect was not obtained with high levels of phosphorus fertilization.…”
Section: Fertilizationmentioning
confidence: 99%